Cultural Differences and Translation - Hongwei, Chen (Meta, 1999)
AbstractThis article discusses the influence of cultural differences on translation'a cross-culturalcommunication event. However complex a culture is, it can roughly be divided into threecategories: material culture, institutional culture and mental culture. Language belongsto institutional culture, which is closely related to mental culture in formation and performance.Differences in mental culture are what produce the differences in languagesinvolved in translation. The article first examines the differences between Chinese andEnglish arising from their respective mental culture, which are mainly manifested inimage and function, integrity and individuality, covertness and overtness, thought andform. It then further provides effective methods to solve culture-bound problems intranslation from Chinese into English.